2020
DOI: 10.1111/papt.12295
|View full text |Cite
|
Sign up to set email alerts
|

Understanding predictors of change in a day treatment setting for non‐suicidal self‐injury

Abstract: Objectives. To examine change in non-suicidal self-injury (NSSI) frequency, quality of life, and functional impairment from admission to discharge in patients enrolled in partial hospitalization and intensive outpatient programmes (PHP/IOP) designed to treat NSSI. Demographic, clinical, and treatment-related predictors of changes were also examined.Design. Data were collected as part of routine clinical assessment procedures at admission and discharge from patients enrolled in a PHP/IOP programme designed to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 69 publications
0
4
1
1
Order By: Relevance
“…These findings contrast with previous research comparing telehealth IOP outcomes by insurance type that found disparities in outcomes for adults [10] as well as disparities in in-person IOP outcomes for children [32], youths [28], and young adults [35]. In studies addressing youths and young adults, these different findings may be explained by the handling of dropout as these studies appear to have included all clients who initiated treatment [28,35]. It may be that there are higher dropout levels among clients on public insurance and that the resulting effect on outcomes from a smaller dose of treatment is inadequate for symptom improvement.…”
Section: Principal Findingscontrasting
confidence: 99%
See 1 more Smart Citation
“…These findings contrast with previous research comparing telehealth IOP outcomes by insurance type that found disparities in outcomes for adults [10] as well as disparities in in-person IOP outcomes for children [32], youths [28], and young adults [35]. In studies addressing youths and young adults, these different findings may be explained by the handling of dropout as these studies appear to have included all clients who initiated treatment [28,35]. It may be that there are higher dropout levels among clients on public insurance and that the resulting effect on outcomes from a smaller dose of treatment is inadequate for symptom improvement.…”
Section: Principal Findingscontrasting
confidence: 99%
“…In the only study identified that collected data from multiple reporters, adolescents in an IOP treating self-harm reported no differences by insurance type, but parents of youths with private insurance reported significantly greater behavior improvement than parents of youths with public insurance [28]. A recent study of an IOP for self-harm examined treatment differences by insurance type with the largest sample to date (n=1327 [35]), finding a significantly greater increase in functioning for youths and young adults on private insurance than for those on public insurance. In each of these cases, the authors note that time and the financial commitments of the intensive program may cause greater stressors for youths and families on public insurance than for those on private insurance.…”
Section: Telehealth Iops Clinical Outcomes and Insurance Typementioning
confidence: 99%
“…In addition to the factor above, we also found that patients with fewer hospitalizations were more likely to have self-injury behaviors, indicating that hospitalization can improve the patient’s condition and prevent the recurrence of NSSI. In a day treatment setting for non-suicidal self-injury, NSSI frequency significantly decreased after hospitalization, while quality of life and functional impairment significantly improved at the same time ( 46 ). Therefore, our lower incidence of NSSI may also be related to inpatients.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our data, NSSI prevention strategies should involve the routine assessment of QoL in adolescents, especially in clinical settings. QoL could, therefore, be an important outcome variable to assess the efficiency of NSSI treatment [115].…”
Section: Discussionmentioning
confidence: 99%